2021
DOI: 10.1021/acs.analchem.1c03010
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Ionic Signal Enhancement with Probe Grafting Density on the Outer Surface of Nanochannels

Abstract: Probe-modified nanopores/nanochannels are one of the most advanced sensors because the probes interact strongly with ions and targets in nanoconfinement and create a sensitive and selective ionic signal. Recently, ionic signals have been demonstrated to be sensitive to the probe−target interaction on the outer surface of nanopores/nanochannels, which can offer more open space for target recognition and signal conversion than nanoconfined cavities. To enhance the ionic signal, we investigated the effect of graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 58 publications
(82 reference statements)
1
12
0
Order By: Relevance
“…Furthermore, the experimental results showed that the ICR ratio decreased with the pore size of the PET nanochannels (Figure S12), which stem from the space compression of the ion-enrichment/depletion region and the corresponding enhancement of the double-layer interaction. 73,74 Both the experimental and theoretical results demonstrated that the change in surface charge by modified PDA in the ion-depletion region leads to the fundamental change in the ICR effect.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Furthermore, the experimental results showed that the ICR ratio decreased with the pore size of the PET nanochannels (Figure S12), which stem from the space compression of the ion-enrichment/depletion region and the corresponding enhancement of the double-layer interaction. 73,74 Both the experimental and theoretical results demonstrated that the change in surface charge by modified PDA in the ion-depletion region leads to the fundamental change in the ICR effect.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…The grafting density of FE OS is related to the ionic signal enhancement. 15 The experimental results show that, when the same amount of analytes is added, the change ratio of the ionic signal increases with the increase of grafting density of FE OS . The numerical simulations show that, with the increase of grafting density of FE OS , the decrease of background current and the aggregation of analytes at the entrance of the pore contribute to ionic signal enhancement.…”
Section: ■ Outer Surface Modified Nanoporesmentioning
confidence: 94%
“…The conformational change of FE OS induced by an applied electric field can control the transport of analytes larger than ions, such as proteins and nanoparticles. The grafting density of FE OS is related to the ionic signal enhancement . The experimental results show that, when the same amount of analytes is added, the change ratio of the ionic signal increases with the increase of grafting density of FE OS .…”
Section: Outer Surface Modified Nanoporesmentioning
confidence: 94%
See 1 more Smart Citation
“…Nanofluidic-based biochemical sensing is a promising approach for high-throughput, high-sensitive, and label-free detection of a wide range of targets, relying on the change of ion transport signals across the nanofluidic membrane. Generally, the ion transport signal through nanofluidic membranes is governed by strong interactions between ion species and membrane surfaces, presenting very different behaviors from those of macroscopic fluids. , In order to realize selective ion/molecule transport, the nanofluidic membrane modified with an ion/molecule recognition agent (ionophores, aptamers, antibodies, etc.) that can selectively bind the target ion/molecule are commonly used. Furthermore, precise regulation of membrane surface properties including surface charge and surface wettability has been demonstrated to be vital for the regulation of ionic signals of biological ion channels and commonly introduced into artificial nanofluidic systems. For example, electrostatic interactions have been widely investigated for the regulation of the nanofluidic ion transport signal and applied in nanofluidic-based biochemical sensing. Our group systematically investigated the critical role of surface charge in ionic signals of nanofluidic-based chemical sensors by precisely adjusting the grafting density of DNA probes in nanoconfinements and found that the enhanced sensing performance can be realized with the tailoring surface and space charge density .…”
Section: Introductionmentioning
confidence: 99%